Communication of Religious Extension Organizations in Developing Religious Moderation in Neglasari District, Tangerang City - Sondi Silalahi; Edi Amin; Tantan Hermansah; Muhammad Fanshoby (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the organizational communication patterns of religious counselors in the Neglasari community in developing religious moderation in Tangerang City and to examine the factors that hinder their communication efforts. The research is grounded in the constructivist paradigm, which holds that observed social realities cannot be generalized. The research adopts a descriptive qualitative approach, utilizing in-depth interviews with religious leaders, the chairman of the Forum for Religious Harmony (FKUB), religious counselors, and community leaders. The findings reveal two main points: first, the organizational communication of religious counselors in the Neglasari community to promote religious moderation is shaped by efforts to maintain interfaith harmony. However, these efforts are often limited to interactions among religious leaders and religious organizations. Second, the barriers to organizational communication among religious counselors in developing religious moderation include a lack of intensive outreach, insufficient government guidance on religious moderation within the community, and, in some cases, community apathy toward government-sponsored activities, which reflects a lack of openness to social engagement.